2021
DOI: 10.1093/intqhc/mzab110
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of patient-reported quality of care in low- and middle-income countries: a four-country survey of person-centered care

Abstract: Background Person-centeredness is a foundation of high-quality health systems but is poorly measured in low and middle-income countries. We piloted an online survey of four low and middle-income countries (LMICs) to identify the prevalence and correlates of excellent patient-reported quality of care. Methods We administered a cross-sectional online survey using Random Domain Intercept Technology to collect a sample of random … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 22 publications
0
15
1
Order By: Relevance
“…This result may be explained by the lower cost of consulting primarily public conventional health care, which are more likely to be utilized by poorer than richer segments of society. 7 Some previous research 3 , 4 , 15 showed an association between younger age, rural residence, female sex, not having health insurance, and difficulties with traveling time and poor health care responsiveness, but we did not find significant differences in our study.…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…This result may be explained by the lower cost of consulting primarily public conventional health care, which are more likely to be utilized by poorer than richer segments of society. 7 Some previous research 3 , 4 , 15 showed an association between younger age, rural residence, female sex, not having health insurance, and difficulties with traveling time and poor health care responsiveness, but we did not find significant differences in our study.…”
Section: Discussioncontrasting
confidence: 81%
“…In comparison, in a four-country study, including India, seen by a pharmacist or drug seller (compared to community health workers and specialists) were more likely to report poor health care quality. 15 Possible explanations for the found differences may be related the better quality of AYUSH and/or THP mainly private services or high expectations among these service users. 8 In addition, large conventional facilities can be compromised with a longer waiting time than smaller AYUSH and THP facilities, and the latter will probably need to build a client base by increasing the quality of nonclinical care provided.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Third, investing in strengthening implementation of client service charter will help to improve the PHC facilities responsiveness to client’s needs and expectations and hence, improving person-centred care. A study conducted in four low- and middle- income countries (LMICs) has shown that improvements in person-centred care are essential for a high quality health system [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unlike panel surveys, no incentives are provided and no personally identifiable information is exchanged. RIWI technology has been described as nonprobability, online intercept sampling [ 9 ], and has been previously employed to assess various topics such as health care quality [ 10 – 12 ], mental illness stigma [ 13 – 15 ], and anti-vaccine sentiment [ 16 ].…”
Section: Methodsmentioning
confidence: 99%